How Culture, Commitment, and OCB Affect Employee Performance in Central Lombok - Agus Muliadi, Lalu; Husnan, Lalu Hamdani; Saufi, Akhmad (International Research Journal of Business Studies, 2025)
This study examines the impact of organizational culture and commitment on employee performance, moderated by Organizational Citizenship Behavior (OCB), within the Regional Secretariat of Central Lombok Regency. Employing a quantitative approach with the census method, the research involves all 107 employees as respondents. Data were collected using Likert-scale questionnaires and analyzed through outer model testing, inner model testing, and hypothesis testing. The findings indicate that both organizational culture and commitment positively and significantly influence employee performance. Moreover, OCB enhances these relationships, emphasizing its role in improving performance outcomes. These results underscore the necessity of fostering a robust organizational culture, strengthening employee commitment, and encouraging OCB to optimize performance. This study provides practical insights for human resource management in government institutions by highlighting strategies to enhance employee performance. Additionally, it contributes to the theoretical understanding of the interplay between culture, commitment, and OCB in shaping organizational success.